The Damascus Document (D) as a Rewriting of the Community Rule (S) - Steudel, Annette 1963- (2012)
The present study undertakes a literary comparison of the Community Rule (S) and the Damascus Document (D). It turns out that D closely follows the textual organization of 1QS V-VII. The long Fourth Admonition in D is in basic parts an elaboration of 1QS V,1-7a. The reference to 1QS V-VII skips the middle part of D, and continues directly in CD XV (1QS V,7b). From there it can be traced, almost verse by verse, until the end of the Penal Code in D. Reference to 1QS V-VII thus covers nearly the whole composition of D. It is lacking only in D’s large middle part, apart from its edges, and in the beginning and end of D, which parallel sections of 1QS I-IV. An interesting role in the further development of D is not only played by the Book of Jubilees, but also by 1QS VIII-IX, which might have been composed by S as a reaction to D’s rewriting of 1QS V-VII, but it also influenced D. As a whole, the Damascus Document is best understood as a rewriting (Fortschreibung) of the Community Rule, although D also shaped S.\n4207 \n4207